The limits of joint-institutional frameworks for sectoral governance in EU-Swiss bilateral relations: Lessons for future relations with the UK - Sandra Eckert (Leibniz Institute for Financial Research SAFE, 2022)
Joint Institutional Frameworks in bilateral relations are circumscribed in policy scope, can lack adequate instruments for dynamic adaptation and provide limited access to decision-making processes internal to the contracting parties. Informal governance, the involvement of private actors as well as rules such as equivalence provide avenues to remedy these limits in bilateral relations in sectoral governance. Through bilateral agreements, the scope of territoriallybound political authority is expanded. The formalised and institutionalised frameworks and bodies established are, however, frequently accompanied by mechanisms of informal cooperation and special rules either to cover policy fields where no contractual relation exists, to provide for flexible solutions where needed, or to involve both public and private actors that otherwise do not have access to formal decision-making bodies. This SAFE working paper conceptualises formal and informal modes of cooperation and varying actor constellations. It discusses their relevance for the case of bilateral relations between the European Union (EU) andSwitzerland in sectoral governance. More specifically, it draws lessons from EU-Swiss sectoral governance of financial and electricity markets for the future relations of the EU with the United Kingdom (UK). The findings suggest that there are distinct governance arrangements across sectors, while the patterns of sectoral governance are expected to look very much alike in the United Kingdom and Switzerland in the years to come. The general takeaway is that Brexit will have repercussions for the EU's external relations with other third countries, putting ever more emphasis on formal and rule-based approaches, while leaving a need for sector-specific cross border co-operation.
Keywords: 330